Drivers of participation elasticities across Europe: Gender or earner role within the household? - Charlotte Bartels; Cortnie Shupe (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
We compute participation tax rates across the EU and find that work disincentives inherent in tax-benefit systems largely depend on household composition and the individual's earner role within the household. We then estimate participation elasticities using an IV group estimator that enables us to investigate the responsiveness of individuals to work incentives. We contribute to the literature on heterogeneous elasticities by providing estimates for breadwinners and secondary earners separately, according to their potential earnings rather than gender. Our results show an average participation elasticity of 0.0-0.1 among breadwinners and 0.1-0.4 among secondary earners in the EU as well as a high degree of heterogeneity across countries.
Keywords: H24; H31; J22; J65; 330; participation elasticities; labor supply; taxation; cross-country comparisons